Breast cancer occult in renal cell carcinoma: a case report of a rare tumor-to-tumor metastasis and literature review - Huang, Bin; Han, Yin; Zhang, Yanjie; Liu, Hongsheng (Frontiers in Oncology, 2025)
Metastasis from breast cancer (BC) to renal cell carcinoma (RCC) is rare. We retrospectively analyzed the clinical data, i.e., medical history, imaging, and laboratory examinations, as well as pathological features of a 62-year-old female with invasive ductal carcinoma of the breast metastasizing to clear cell renal cell carcinoma (CCRCC). A comprehensive literature review was also conducted. Her right breast mass was pathologically diagnosed as invasive ductal carcinoma eight months ago. A large mass in the left kidney was incidentally discovered during a computed tomography (CT) scan, which was consistent with RCC. She underwent neoadjuvant chemotherapy, radical mastectomy, and endocrine therapy, as well as laparoscopic left nephrectomy four months postoperatively. Her pathological examination revealed two heterogeneous tumor components in the kidney: typical CCRCC [CD10+, Vimentin+, carbonic anhydrase IX (CAIX)+, paired box gene 8 (PAX-8)+, 3% Ki-67 proliferation index) as well as multifocal metastatic invasive ductal carcinoma of the breast (estrogen receptor (ER) 50%+++, GATA binding protein 3 (GATA3) +, Human epidermal growth factor receptor-2 (HER-2) 1+, and 20% Ki-67 proliferation index). These findings met the diagnostic criteria for TTM. She also continued BC endocrine therapy postoperatively. However, no recurrence or metastasis was observed during the 11 follow-up months.